ANALISIS BIAYA USAHATANI KACANG TANAH DI PROVINSI JAWA BARAT - Neneng Nur Aida; Lilis Imamah Ichdayati; Iwan Aminudin (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2022)
The research was conducted to analyze cost of production and labor in peanut farming in West Java. The research was conducted in June-September 2021, in 6 (six) districts (Garut, Cianjur, Sumedang, Tasikmalaya, Subang and Purwakarta) in West Java province. The sampling method in this research is grouping based on area (proportional cluster sampling), with the number of respondents being peanut farmers as many as 507 people. The research used descriptive analysis with a Pivot Table Excel calculation tool. The results showed that the cost of peanut farming in West Java was influenced by the cost of labor and production inputs, namely the labor cost of 52.28%; seed cost of 35.04%; and the cost of fertilizers and pesticides by 7.61%. Where labor costs are the largest and dominate in peanut farming. The highest percentage ratio is in Cianjur Regency as the center of peanuts